2023
DOI: 10.1111/all.15850
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell silencing: A novel therapeutic approach for urticaria and other mast cell‐mediated diseases

Martin Metz,
Pavel Kolkhir,
Sabine Altrichter
et al.

Abstract: Chronic urticaria (CU) is a mast cell (MC)‐dependent disease with limited therapeutic options. Current management strategies are directed at inhibiting IgE‐mediated activation of MCs and antagonizing effects of released mediators. Due to the complexity and heterogeneity of CU and other MC diseases and mechanisms of MC activation—including multiple activating receptors and ligands, diverse signaling pathways, and a menagerie of mediators—strategies of MC depletion or MC silencing (i.e., inhibition of MC activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…These observations suggest that IL-33's influence in CSU extends beyond that of a biomarker, acting as a pivotal mediator in the disease's pathogenesis and affecting both clinical outcomes and patient well-being. The significant correlation between IL-33 with the UAS7 and DLQI scores underlines the necessity for developing IL-33-targeted therapeutic approaches, especially for patient subgroups inadequately managed by current treatments, such as omalizumab [26,27]. The findings by Manti et al [28] support this approach, emphasizing the potential of monoclonal antibodies in enhancing CSU management.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These observations suggest that IL-33's influence in CSU extends beyond that of a biomarker, acting as a pivotal mediator in the disease's pathogenesis and affecting both clinical outcomes and patient well-being. The significant correlation between IL-33 with the UAS7 and DLQI scores underlines the necessity for developing IL-33-targeted therapeutic approaches, especially for patient subgroups inadequately managed by current treatments, such as omalizumab [26,27]. The findings by Manti et al [28] support this approach, emphasizing the potential of monoclonal antibodies in enhancing CSU management.…”
Section: Discussionmentioning
confidence: 97%
“…The potential for targeting these cytokines to mitigate the symptoms of CSU represents an intriguing and scientifically promising avenue for exploration. While the effectiveness of such therapeutic interventions has yet to be definitively proven, the development of biologic therapies aimed at these pathways, including tezepelumab (anti-TSLP), etokimab, and itepekimab (both targeting IL-33), as well as astegolimab and GSK3772847 (targeting the ST2 subunit of the IL-33 receptor), are currently undergoing clinical evaluation [26,27]. This innovative therapeutic strategy marks a significant shift in the approach to managing CSU, offering the potential to transform patient outcomes by addressing the underlying mechanisms of the disease directly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cells express inhibitory molecules, such as Siglec-8, Siglec-6 and CD200R. The activation of these molecules expressed on mast cells and diminishes histamine release (Metz et al 2023). The low-affinity IgG receptor (Fc γ R2b), which contributes to supra-optimal negative regulation of Fc ε RI-induced mast cell activation is another candidate of a player in the disappearance phase (Gast et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In children with DCM, who usually display severe MC mediator-related symptoms, new drugs capable of reducing the pathogenic MC activity may turn out to be more effective and less toxic than MC depleters, such as tyrosine kinase inhibitors. MC activation antagonists, including omalizumab, for which only a few uncontrolled studies showing response in children with CM have been reported so far, or other monoclonal antibodies that engage inhibitory receptors (e.g., lirentelimab), might prove to be effective and become true therapeutic options in the near future [ 96 , 108 , 109 ]. Currently, early clinical trials of new drugs believed to reduce pathogenic MC activity are ongoing, which provides hope for patients with various MC disorders.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%